2022
DOI: 10.3390/cancers14225526
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8A Is a Promising Prognostic Biomarker and Therapeutic Target for Pancreatic Adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is a highly malignant tumor of the digestive system with increasing morbidity and mortality. The lack of sensitive and reliable biomarkers is one of the main reasons for the poor prognosis. Volume-regulated anion channels (VRAC), which are ubiquitously expressed in the vertebrate cell membrane, are composed of leucine-rich repeat-containing 8A (LRRC8A) and four other homologous family members (LRRC8B–E). VRAC heterogeneous complex is implicated in each of the six “hallmarks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In PAAD, LRRC8A is associated with cell proliferation, migration, drug resistance, and immune infiltration [ 9 ]. Moreover, investigation of the LRRC8A gene’s co-expression and its network in PAAD patients has revealed prominent enrichment of genes situated close to LRRC8A in the PI3K-AKT and focal adhesion pathways [ 9 ]. On the contrary, detailed functions and interactions of VRAC in colon cancer are not yet clear and subjected of discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PAAD, LRRC8A is associated with cell proliferation, migration, drug resistance, and immune infiltration [ 9 ]. Moreover, investigation of the LRRC8A gene’s co-expression and its network in PAAD patients has revealed prominent enrichment of genes situated close to LRRC8A in the PI3K-AKT and focal adhesion pathways [ 9 ]. On the contrary, detailed functions and interactions of VRAC in colon cancer are not yet clear and subjected of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in recent years, there has been a growing interest in anion channels, i.e., chloride (Cl) channels. These channels play a vital role in various cellular processes and their abnormal expression and/or function is associated with various human diseases, such as cystic fibrosis, myotonia, epilepsy, hyperekplexia, lysosomal storage diseases, deafness, renal salt wasting, kidney stones, osteopetrosis and numerous tumour development of numerous types of tumours [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…VRAC has been suggested to be one of these ion channels. Indeed, while pharmacological or molecular biological inhibition of VRAC did not detectably impair migration of various cell types in a study using a wound-healing assay ( Liu and Stauber, 2019 ), other studies reported VRAC influenced the motility of a wide range of cancer cells such as colorectal cancer ( Fujii et al, 2018 ), glioblastoma ( Rubino et al, 2018 ; Wong et al, 2018 ), human colon cancer ( Zhang et al, 2018 ), hepatocellular carcinoma ( Lu et al, 2019 ), pancreatic adenocarcinoma ( Xu et al, 2022 ) and breast cancer ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when either LRRC8A or LRRC8D is knocked out, cancer cells exhibit a higher tolerance towards these platinum-based medications ( Planells-Cases et al, 2015 ). LRRC8 genes have been implicated in drug resistance and prognosis in various cancer types ( Sørensen et al, 2016 ; Xu et al, 2020 ; Siemer et al, 2021 ; Widmer et al, 2022 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leucine-rich repeat protein A (LRRC8A), also known as SWELL1, is a core component of anionic channels (VRAC) [50]. LRRC8A is closely associated with the occurrence of multiple tumors [51][52][53].…”
Section: Discussionmentioning
confidence: 99%